Perlukah Akta Hasutan bagi menjamin perpaduan kaum di Malaysia? Is Sedition Act needed for maintaining racial stability in Malaysia? - Mohd Shariff, Roos Niza (2014)
Sedition Act 1948 is a Malaysian law that provides sentence for seditious acts. However, there was a suggestion to abolish this Sedition Act because it hinders the freedom of speech and thus contrary to Article 10 of the Federal Constitution. Nonetheless, freedom of speech should has a limitation.The methodology of qualitative research is done with the use of analytical study of case laws, provisions of law and literature review.The objectives of research are for better understanding of the needs, applicability, obstructions and impacts facing the implementation of Sedition Act in Malaysia.Research findings showed that from the substantive and procedural aspect, Sedition Act has been in practice since the British occupation for the purpose of keeping the unity of people.Research findings also narrowed down to the difficuilties in applying a complete and correct understanding regarding sedition act in a muti racial society with varies religions.This working paper concluded that the implementation of Sedition Act in Malaysia is needed as the provisions in the Act are able to uphold and protect the national unit of multi racial in Malaysia.